О нахождении на Украине Daphnia curvirostris Eylmann, 1887 - Радзимовский, В.Д. (Вестник зоологии, 1982)
Daphnia curvirostris is reported for the first time from five localities in the Ukrainian Polessie area. The description of male and female is given to show the main differences from D. pulex, with which it was often confused.